Dengeki Daisy. Vol. 1 - Motomi, Kyousuke (Viz Media, 2010)
"After orphan Teru Kurebayashi loses her beloved older brother, she finds solace in the messages she exchanges with Daisy, an enigmatic figure who can only be reached through the cell phone her brother left her. Meanwhile, mysterious Tasuku Kurosaki always seems to be around whenever Teru needs help. Could Daisy be a lot closer than Teru thinks?"--Cover.